Fibonacci polynominals of order k, multinomial expansions and probability - Andreas N. Philippou; Costas Georghiou; George N. Philippou (International Journal of Mathematics and Mathematical Sciences)
The Fibonacci polynomials of order k are introduced and two expansions of them are obtained, in terms of the multinomial and binomial coefficients, respectively. A relation between them and probability is also established. The present work generalizes results of [2] - [4] and [5].